Clinical characteristics of patients with choroidal melanoma of small sizes - Tsukanova, I.V. (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Coroidal melanomas (CM) of small sizes, that include CM with height up to 3.0-4.0 mm, comprise 5-21% among all melanomas. According to international TNM classification (2009), T1 CM stage includes melanomas protruding into the vitreous up to 3.0 mm and having the base length up to 12.0 mm and melanomas protruding from 3.1 to 6.0 mm and having the base length up to 9.0 mm. Thus, CMs of small sizes (T I stage) refer to melanoma protruding up to 3.0 mm and having the base length up to 12.0 mm Since CM can be early diagnosed as result of active improvement of diagnostic methods, there is a need of an extended use of organ-sparing treatment modes, in which successful local result, so called local control, and favorable life prognosis for patients can be expected. In view of this, close investigation of different tumor characteristics which can help in choosing adequate treatment approach and in predicting its endpoint is of a great necessity and relevance. The purpose of the present paper was to study clinical characteristics of T1 CM stage (protruding to the vitreous up to 3.0 mm and the base length up to 12.0 mm) in patients treated at State Institition “The Filatov Institute of Eye Diseases of Tissue Therapy of NAMS of Ukraine” Material and Methods. We studied case histories of 88 patients with CM of small sizes received medical treatment at SI “The Filatov Institute of Eye Diseases of Tissue Therapy of NAMS of Ukraine”within 2004 and 2016. All patients underwent standard ophthalmological and general examination Сine-Scan ultrasound sonography, liver ultrasound test, and lung fluorography/roentgenography. At the moment of referral, none of patients were revealed metastasis signs. Statistical data were processed using “Statistic 9.0” software. Mean values are given as М(SD). Results. T 1 CM stage was observed almost 2.5 times more often in women (71.6%) as compared to men affecting working-age persons, average age 55.9 (12.8) y/o. At baseline of treatment at SI “Filatov Institute of Eye Diseases and Tissue Therapy”, CMs of small sizes were mainly of paracentral and juxtapapillary lacation, 37 (42.05%) and 26 (29.55%) patients, respectively; tumor protruding averaged 1.89(0.73) mm and mean tumor base length was 7.36 (2.2) mm. In 86 patients (96.74%) the tumor base length exceeded 3 mm. Unevenly pigmented tumors were observed rarely, only in 5 patients (5.68%). The tumor borders were indistinct in most cases (88.64%). Conclusions. Clinical characteristics of T1 CM stage were studied at baseline on dependence of sex, lacation, size, pigmentation, and tumor growth.